Ergonomic Risk and Work Fatigue among Mining Workers in KertaBuana Village - Muhammad Rizky Amalia; Emilia Sophie Tandiera; Novita Yuliana Ferdinand; Suryani Noer Wahyudi; Tathia Rizky Amalia; Venuta Della Pasqua; Dewi Novita Hardianti (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Mining workers in Kerta Buana Village are exposed to long working hours and heavy physical workloads, increasing the risk of musculoskeletal disorders and chronic fatigue. Ergonomic awareness and occupational safety training remain limited, contributing to higher health complaints among workers. Objective : To identify the prevalence of ergonomic risks and work fatigue symptoms related to long working hours among mining workers in Kerta Buana Village. Research Methods/ Implementation Methods : A descriptive survey was conducted involving mining workers using a structured questionnaire to collect data on working hours, physical complaints, and participation in occupational health and safety (OHS) training. Data were analyzed using descriptive statistics to determine risk proportions. Results : The findings showed that 87.5% of respondents worked more than eight hours per day, and 62.5% reported back pain or muscle fatigue. Around 54.2% had never attended any OHS training, indicating a lack of ergonomic awareness and preventive practices at the workplace. Conclusion/Lesson Learned : Prolonged working hours and insufficient ergonomic training contribute to high levels of fatigue and musculoskeletal complaints among mining workers. Improving ergonomic practices and providing regular OHS education are essential to reduce health risks and enhance workers’ well-being.